Risk management: Clean water crisis mitigation efforts in Indonesia with rain water harvesting and reverse osmosis innovations - Rahman Fajar Irnawan (Energy Justice, 2024)
Background: Water is an important component for living things on earth, so water cannot be separated from human life. This is because the human component consists of 70% water in it. The increase in population and polluted water sources has caused humans to experience a clean water crisis, thereby hampering human socioeconomic life on earth. Findings: Considering that Indonesia has a fairly high rainfall, namely 2,702 mm3 per year, and has polluted water sources and a large sea area, the innovative idea of using rainwater harvesting and reverse osmosis is a solution to overcome problems and be able to overcome the risk of a clean water crisis in the future. front. Discussing the clean water crisis in Indonesia, the area that has this problem is one of the DKI Jakarta areas, namely, Muara Angke, Pluit, and North Jakarta. Methods: In writing this idea, systematic literature reviews and article reviews were used. The systematic method of the literature review is collecting metadata obtained according to the journal database via https://scholar.google.com/ and visualizing it using VOSviewer. This is intended to show research trends regarding clean water technology. Conclusion: Three blocks have a water shortage crisis, namely the Waste Block, the Eceng Block, and the Empang Block. The scarcity of clean water in this area is caused by illegal land issues which makes it difficult to obtain permits for piping systems from the PDAM and the contamination of springs due to the influence of geographical location. The implementation of this technology is considered quite simple in the community so it can be a solution to the clean water crisis problem.Of course, the treated water is expected to meet the parameters of clean water, namely the Ministry of Health Regulation Number 32 of 2017 concerning sanitation water and the Ministry of Health Regulation Number 492 of 2010 concerning drinking water quality standards. So that the water can be utilized by the people of Indonesia.